Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan Unit Keamanan pada PT Bank Rakyat Indonesia Cabang Jakarta Barat - Renaldi Tarigan; Aden Prawiro Sudarso (Universitas 45 Surabaya, 2024)
This research aims to analyze the influence of work discipline and work environment on employee performance. This type of research is quantitative research with primary data sources. The population in this study were employees of PT. Bank Rakyat Indonesia's West Jakarta branch security unit in 2020-2022 numbered 159 people. The sample selection method used in this research was the Solvin method so that the sample obtained using this method was 61 respondents. Y = -0.067 + 0.455X_1 + 0.319X_2. Partial research results on the independent variable Work Discipline have a significant effect on the dependent variable Employee Performance of 79.8%, hypothesis testing obtained T count > T table or (15.263> 2.0017). Partial research results of independent variables in the Work Environment have a significant effect on the Employee Performance variable by 78.8%, hypothesis test T count > T table or (14.815 > 2.0017). Work Discipline and Work Environment simultaneously have a significant effect on the dependent variable Employee Performance by 86.8%, hypothesis testing obtained calculated F > F table or (190.055 > 3.16).